Passive seismic unseating prevention strategies implemented in highway bridges: A state-of-the-art review. (1st September 2019) - Xiang, Nailiang; Goto, Yoshiaki; Obata, Makoto; Alam, M. Shahria
Highlights: Typical bridge unseating damages in past earthquakes are introduced. Specifications on unseating prevention in modern bridge codes are summarized. Minimum support length and seismic restrainers are effective measures to prevent unseating. The seismic performance of various passive unseating prevention restrainers for highway bridges is reviewed. Abstract: Recent major earthquakes worldwide demonstrated extensive bridge collapses caused by span unseating, which highlights the necessity of implementing effective unseating prevention measures in bridges. This state-of-the-art review provides an informative overview of the recent developments of passive unseating prevention measures for highway bridges against earthquakes, which primarily include minimum support length requirements and unseating prevention restrainers. Important aspects of these strategies in terms of their effectiveness, limitations, and future research needs are summarized and discussed. The current study synthesizes the existing information on bridge unseating prevention strategies, presents in a concise manner in the form of useful equations, tables, and figures, and explains the critical aspects for implementing these strategies. The results of this study are expected to motivate researchers and practicing engineers to extend implementation and innovation of bridge unseating prevention strategies.